Borataalkene or Boratabenzene? Understanding the Aromaticity of 9-Borataphenanthrene Anions and Its Central Ring - Pino-Rios, R (Royal Society of Chemistry, 2020)
The recently synthesized 9-borataphenanthrene anion (1) shows a reactivity in its central ring that resembles both a cycloalkene and an aromatic ring. Computational studies using the magnetic approach support these results. However, due to the limitations that the use of a single criterion can offer, a complete analysis was performed using multiple aromaticity criteria including magnetic, geometric, electron delocalization, reactivity and orbital localization in order to elucidate the nature of the six-membered rings in 1. Our results show that the outer rings in 1 exhibit an aromatic character similar to benzene, while the central ring is better described as an (cyclo)alkene. Additionally, it is shown that assessments using various criteria allow a complete understanding of aromaticity in polycyclic systems. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.